Photoshop Elements 4.0 Maximum Performance - Galer, Mark (Focal Press, 2012)
You will learn how to create professional quality digital images with Photoshop Elements 4.0 without the need to upgrade to Photoshop with this unique guide from best-selling author Mark Galer. This complete package of book and DVD walks you through Elements' powerful and less well-known post-production editing techniques showing you how to get maximum results from this low-price program. A series of creative projects, packed with tips and tricks and illustrated with large, full-color screengrabs, guide you through a wide range of advanced techniques for professional quality editing. Including coverage of new Elements 4.0 features, the straighten tool and the auto extraction tool, all the main features of Elements are covered - camera RAW, 16 bit editing, Healing Brush, Shadows/ Highlights, Reduce Noise and much more. The projects are supported by a DVD containing 4 hours of QuickTime movie tutorials, over 200 high-resolution images as well as loadable presets. Completed multi-layered project files are also available on the DVD so that you can compare and analyse these projects against your own. All the content is suitable for Mac users. Visit the book's webpage on www.focalpress.com for information on how to adapt keyboard modifier keys when using the keyboard shortcuts. Other Photoshop Elements 4.0 titles published by Focal include Adobe Photoshop Elements 4.0: a visual introduction to the program for those starting out in digital imaging; Advanced Photoshop Elements 4.0 for Digital Photographers: an advanced book aimed at photographers; Adobe Photoshop Elements 4.0 A-Z: an alphabetical listing of the main features of Elements, with shortcut keys and techniques.